Study on the stabilization mechanisms of wet-milled cepharanthine nanosuspensions using systematical characterization. (1st February 2020) - Fu, Tingting; Gu, Xiangshuai; Liu, Qiang; Peng, Xiaodong; Yang, Jianhong
Abstract: Objectives: Stability issues are inevitable problems that are encountered in nanosuspension (NS) technology developments and in the industrial application of pharmaceuticals. This study aims to assess the stability of wet-milled cepharanthine NSs and elucidate the stabilization mechanisms of different stabilizers. Methods: The aggregation state was examined via scanning electron microscopy, laser diffraction, and rheometry. The zeta potential, stabilizer adsorption, surface tension, and drug-stabilizer interactions were employed to elucidate the stabilization mechanisms. Results: The results suggest that croscarmellose sodium (CCS), D-α-tocopherol polyethylene glycol 1000 succinate (TPGS), or polyvinyl pyrrolidone VA64 (PVP VA64) alone was able to prevent nanoparticle aggregation for at least 30 days. Attempts to evaluate the stability mechanisms of different stabilization systems revealed that CCS improved the steric-kinetic stabilization of the NSs, attributed to its high viscosity, swelling capacity, and physical barrier effects. In contrast, the excellent physical stability of TPGS systems was mainly due to the reduced surface tension and higher crystallinity. PVP VA64 can adsorb onto the surfaces of nanoparticles and stabilize the NS via steric forces. Conclusion: This study demonstrated the complex effects of CCS, TPGS, and PVP VA64 on cepharanthine NS stability and presented an approach for the rational design of stable NSs.